FY15-FY17 MNA Business Planning - Biswas, Shanu (World Bank, Washington, DC, 2014)
The new Bank structure that is to come into force on July 1, 2014 will bring with it a new business planning structure. This MNA K&L fast brief provides a brief overview of this process. The focus here is on the Regions however some light is also shed on the budgeting process on the side of the Global Practices (GPs) and the Cross-Cutting Areas of Engagement (CCSAs).